EFEKTIVITAS MODEL PEMBELAJAAN DAN KEMAMPUAN BERPIKIR ANALITIK TERHADAP PEMAHAMAN ALJABAR SISWA KELAS VII SMP - Sanusi Sanusi; Dirgantara Wicaksono (Taksasila Edukasi Insani, 2025)
This study aims to examine the effectiveness of the Problem-Based Learning (PBL) model with a deep learning approach and students’ analytical thinking skills on algebra comprehension among seventh-grade students at SMP Muhammadiyah Cianjur. Using a 2×2 factorial quasi-experimental design, the study involved 60 students who were divided into experimental and control groups. The experimental group was taught using the PBL model with a deep learning approach, while the control group received instruction using the Project-Based Learning (PjBL) method. Students were also categorized into high and low analytical thinking groups based on pretest scores.Data were collected through tests measuring analytical thinking and algebra comprehension, and analyzed using two-way ANOVA. The findings indicate a significant effect of the learning model on students’ algebra comprehension. Students taught with the PBL model achieved higher learning outcomes compared to those taught with PjBL. Furthermore, students with high analytical thinking skills demonstrated better comprehension than those with lower analytical abilities. A significant interaction was also found between the learning model and analytical thinking skills, indicating that the effectiveness of the PBL model is more pronounced among students with higher analytical thinking. These results suggest the importance of selecting appropriate instructional models and recognizing students' cognitive abilities in designing mathematics learning strategies.Keywords: Problem-Based Learning (PBL); Deep Learning Approach; Analytical Thinking; Algebra Comprehension; Junior High School Students